Talented Youths or Dangerous Criminals? Exploring Judicial Attitudes in the Sentencing of Data Crime Cases in Chinese Courts - Zhang, Yujie (Criminal justice and behavior, 2025)
The focal concerns framework stands as the leading theoretical approach in criminology to account for differences in sentencing outcomes. Despite extensive empirical research, this framework has yet to be thoroughly examined in the context of cybercrime or data crime and in non-Western legal cultures. This study examines the following question: to what degree and in what ways do Chinese judges take into account the original focal concerns of blameworthiness, protecting the community, and practical limitations when making their sentencing decisions? By analyzing 2,052 cases and focusing on 34 detailed sentencing remarks from cases adjudicated in China from 2013 to 2023, along with insights from semi-structured interviews with 14 judges specializing in data crime, our research indicates that sentencing decisions in data crime cases in China are consistently shaped by the blameworthiness and community protection, although rather different factors associated with these concerns impact the assessment of data crime case severity.